Computational design methods and technologies applications in CAD, CAM, and CAE education - Gu, Ning, 1975-; Wan, Xiangyu, 1979- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2012)
"This book explores state-of-the-art developments in computational design methods and their impact on contemporary design education, offering case studies, empirical research findings, pedagogical theories, and reflections"--Provided by publisher.